Partisipasi Masyarakat dalam Program Nasional Pemberdayaan Masyarakat-Mandiri Di Desa Kotabatu, Kecamatan Ciomas, Kabupaten Bogor - Nurul Fitriyanti; Dwi Sadono (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2013)
This research focuses on community participation in the Program Nasional Pemberdayaan Masyarakat-Mandiri in Kotabatu Rural, District Ciomas, Bogor Regency. This study uses quantitative with survey methods and qualitative methods with in-depth interviews. Respondents in this study amounted to 45 people and are selected by random sampling method. The purposes of this study are 1) to analyze the correlation of internal factors in the community with the level of participation in PNPM-Mandiri, 2) to analyze the correlation of external factors that exist in the community with the level of participation in PNPM-Mandiri, and 3) to analyze the correlation between community participation the level of achievement gained in the community-PNPM Mandiri program. Based on the research results to internal factors that influence is age and external factors that influence is intensity of communication. In this program, people participate less, but people still feel a high level of achievement.Keywords: Participation, internal factors, external factors, and achievement.